Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Matematika di Sekolah Dasar - Natasya Febriyanti; Asep Rudi Nurjaman (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This research is motivated by the fact that there are still many students who make mistakes in solving math word problems so that this study aims to describe students' mistakes in solving math word problems at elementary schools. Based on research that has been done by researchers using a qualitative descriptive method with the subject of research being a class teacher at one of the elementary schools in Bandung district, various student errors were found in solving math word problems, namely: (1) some of them did not understand the problem as a whole; (2) difficulties in extracting important information; (3) did not specify the exact operation; (4) wrong in applying mathematical operations; (5) does not verify answers. There are also solutions obtained based on interview results including: (1) exercises that focus on understanding concepts; (2) problem solving models; (3) story problem modeling exercises; (4) group discussion and collaboration; (5) emphasis on understanding context; (6) Structured evaluation. The data collection technique was carried out by interview, observation, and documentation techniques